2023
DOI: 10.58235/sjpa.v27i2.10966
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Effects of Co-creation on Outcomes of Public Service Innovation – A Comparative Analysis at the National and Local Government Level in Norway

Abstract: Co-creation in public service innovation is a prominent research field, but few have empirically investigated its effect on the outcomes of innovation. This paper contributes with empirical-based knowledge on the effect of participatory user involvement and other user-oriented methods on public innovation outcomes in different contexts. By employing qualitative comparative analysis (QCA) based on a survey of innovation activities of Norwegian public administration agencies, this article identifies several conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…In one instance, a qualitative comparative analysis of digital platforms in France, Italy, and the United Kingdom showed that e-voting at collaborative platforms in the United Kingdom encompassed the ability to vote online to choose among different proposals and reach a common decision and also an online consultation based on questionnaires and closed answer forms and e-petitions (De Blasio & Selva, 2019). A qualitative comparative analysis of a survey of innovation activities of Norwegian public administration agencies identified a positive relationship between user input and service outcomes (Gesierich, 2023). These studies reveal that voters and authorities consider the potential association of their online deliberation and voting with open government policies.…”
Section: Available Research Of Open Government Policy Votingmentioning
confidence: 99%
“…In one instance, a qualitative comparative analysis of digital platforms in France, Italy, and the United Kingdom showed that e-voting at collaborative platforms in the United Kingdom encompassed the ability to vote online to choose among different proposals and reach a common decision and also an online consultation based on questionnaires and closed answer forms and e-petitions (De Blasio & Selva, 2019). A qualitative comparative analysis of a survey of innovation activities of Norwegian public administration agencies identified a positive relationship between user input and service outcomes (Gesierich, 2023). These studies reveal that voters and authorities consider the potential association of their online deliberation and voting with open government policies.…”
Section: Available Research Of Open Government Policy Votingmentioning
confidence: 99%